(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mental health ad well being is the main thing which makes the human body production or the cells in the body gets active out of that. However the current scenario is not like that the mental health of men and women are different and having a lot of negative things happening that re affecting the brain to produce less. The current study is going to develop the comparison of the mental health of men and women and the different impactful aspect related to the different aspects ofthe mental health and its vacillations. The study is also going to verify the current colleges of another impact on the mental health and their related consequences. The study is also going to provide the statistical information about the live reviews of differentoption regarding the same topic.